Notes on administrative coercion: public authorities' precautionary measures (Revista do Tribunal Regional Federal da 3ª Região, 2011)
This simple article aims to unveil a subject that doctrine contends is obvious: Administrative Law is based, or sustained, on two basic principles, because without them it would not be possible to understand and apply it, especially in the relationship between the state and private individuals (administrative relationship). Although they are well known, they cannot be mentioned enough: the supremacy of the public interest over that of the private individual and the unavailability of the public interest. These “legal vectors” can be considered logical-legal concepts, due to their universality and a priori apprehension, regardless of positive law - at least in countries that adopt the continental European model of Administrative Law. However, they have legal composure to the extent of the order itself, which gives them their [legal] tone. Because of these basic principles, the Administration has [public] prerogatives; in this work, we will highlight the possibility of it directly or indirectly constraining the private individual, using [administrative] coercion; which, however, can only be an extreme measure (ultima ratio). Along these lines, the analysis also refers to (a) the fundamental forms of coercion, in other words, how it “manifests” itself, or presents itself, to the administered, with more detailed mention of the Public Administration's precautionary measures; as well as (b) the enforceability of the administrative act, direct coercion “arising from” the [administrative] act, an extreme measure, the effect of the Public Power's claim, never an attribute or element of the act. Far from exhausting the subject, we have tried to reflect on some important points of Administrative Law.
Keywords: administrative coercion; precautionary measures; enforceability of the administrative act